2008
DOI: 10.3742/opem.2008.8.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Biochemical studies on Telescopium telescopium - a marine mollusk from the Mangrove regions

Abstract: SUMMARYThe tissue extract (TTE) of a marine snail Telescopium telescopium, collected from the coastal regions of West Bengal, India, was extensively screened for pharmacological and biochemical properties. Telescopium telescopium (TTE) produced significant lysis of washed rat erythrocytes (both direct and indirect), produced haemorrhagic lesions in the skin and also released haemoglobin (in vitro tissue damage) from different tissue samples. TTE was found to produce pro-inflammatory effects when injected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Secretions from the mollusks (around 15) were pooled in a sterile container. An aliquot of pooled sample was defatted using dichloromethane (DCM) (Samanta et al 2008b ) for protein fractionation (discussed below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretions from the mollusks (around 15) were pooled in a sterile container. An aliquot of pooled sample was defatted using dichloromethane (DCM) (Samanta et al 2008b ) for protein fractionation (discussed below).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, investigations were taken up in our laboratory for evaluation of pharmacological and biochemical properties of Telescopium telescopium (tissue extract and blue secretion). Earlier studies revealed neuro-pharmacological (Samanta et al 2008a ) haemolytic, pro-inflammatory and hypotensive properties (Samanta et al 2008b ) of tissue extract of Telescopium telescopium. The pharmacological and antimicrobial properties of spermathecal gland of Telescopium telescopium has also been reported (Datta et al 2010 ; Pakrashi et al 1992 ; Pakrashi et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%